Comparative study of the mandarin hybrid fruit characteristics: Nova, Murcott and Ortanique in Capão Bonito SP, Brazil Estudo comparativo das características dos frutos dos híbridos de tangerina: Nova, Murcott e Ortanique, na região de Capão Bonito, SP - Rogério de Sá Borges; Rose Mary Pio (Revista Brasileira de Fruticultura, 2003)
The Murcott tangor represent 20% of the tangerines trees in São Paulo State being the second more grown. Their fruits have good acceptance in the market cause of the good characteristics presented as: size, attractive internal and external color, transport resistance, high juice rate and industry potential. It is necessary to study the behavior of others varieties, in order to amplify the diversity of tangerine industry, which show suitable characteristics to the fresh fruit market and that make possible different harvest season. Many tangerine varieties, selected from the Citrus Germplasm Bank of the do Centro Avançado de Pesquisa Tecnológica do Agronegócio de Citros "Sylvio Moreira"/IAC, belong to trials carried out in 15 places in São Paulo State. The Capão Bonito area, south-west of the state, is one of this places where the Nova tangelo, the Ortanique and the Murcott tangors are showing quite good results about their fruit qualities. This paper had as an objective to compare the fruit characteristics of the Nova tangelo, the Murcott and the Ortanique tangors grafted on two rootstocks: Rangpur lime and Cleopatra mandarin. Accordingly to the gotten results, is possible to conclude that Nova and Ortanique had shown weight, width, fruit shape and juice percent, similar to the Murcott. In compliance with the harvest season, the Nova present suitable conditions to fresh fruit market in May and June. By the other hand the Murcott fruits can be harvested in July to August and the Ortanique in August to September. For this reason, is possible extend the harvest season of this mandarin-like, from two to five month, occurring inclusive in a period out of the crop at the north hemisphere. O tangor Murcott representa 20% das tangerinas plantadas no Estado de São Paulo, sendo a segunda mais cultivada. Seus frutos têm excelente aceitação no mercado por apresentar boas características como tamanho adequado para o consumidor, coloração alaranjada forte tanto de casca quanto de polpa, resistência ao transporte, alto rendimento de suco e potencial para industrialização. Há necessidade de estudar o comportamento de outras variedades, para ampliar a diversidade da cultura da tangerina, que apresentem adequadas características para o mercado de fruta fresca e que possibilitem diferentes épocas de colheita. Diversas variedades de tangerinas, pré-selecionadas no Banco Ativo de Germoplasma de Citros, do Centro Avançado de Pesquisa Tecnológica do Agronegócio de Citros "Sylvio Moreira"/IAC/APTA fazem parte de experimentos conduzidos em 15 localidades do Estado de São Paulo. A região de Capão Bonito, situada no sudoeste paulista, constitui um dos locais onde o tangelo Nova e os tangores Murcott e Ortanique vêm apresentando resultados bastante satisfatórios quanto à qualidade de seus frutos. Avaliou-se neste trabalho, as características físico-químicas do tangelo Nova e dos tangores Murcott e Ortanique nos porta-enxertos limão Cravo e tangerina Cleópatra. Nova e Ortanique apresentaram valores de massa, diâmetro e forma do fruto e rendimento de suco, semelhantes aos do tangor Murcott. Quanto ao período de colheita, os frutos da variedade Nova apresentaram condições adequadas para consumo em maio e junho, já os frutos de Murcott podem ser colhidos em julho e agosto e a Ortanique em agosto e setembro. Assim sendo, há possibilidade de estender o período de safra desse grupo de tangerina, de dois para cinco meses, vindo inclusive a ocorrer num período de entressafra no hemisfério norte.